Opazovanje socialne anksioznosti ob predstavitvi seminarske naloge - je vidna očem zunanjega opazovalca? - Šterman Ivančič, Klaudija (Šolsko polje, 2010)
In this article we deal with social anxiety from the point of view of a socially anxious individual in the process of adult education. More precisely,in the context of the so called active methods of teaching, which are nowadays in the forefront of adult education and higher education as well.We present the results of the research which helped us ascertain whether it is possible to identify exterior indicators of social anxiety in the process of education. Th e research was executed on the sample of university part-time students (N = 28). We undertook the study of social anxiety multilaterally by using questionnaires as well as observing the participants during the actual socially evaluative situation (seminar presentation). Due tonot being available in our country, we have created a special questionnaire within the research for measuring the presence of social anxiety in the process of adult education. Th e instrument has proved itself to be very reliable for the needs of the research thus it is presented in this articleTh e results of the research show that there is no essential diff erence between socially more and socially less anxious students in the fi eld of seminar presentation according to the defi ned criteria of a good presentation. Th e results indicate the complexity of the social anxiety phenomenon in the education process which is dealt with and explained through multilateral interpretation of data. At the same time we try to point out the way we as educators can improve the quality of the process itself for all involved in the preparation of education by taking social anxiety into consideration. We also warn of the importance of clearly defi ned goals of education, clear requirements and criteria of knowledge and transparency of the education process. Procedures that seem to be in the background while putting more and more emphasis on the adaptability of the process to the needs and experiences of individuals (prior experiences and knowledge of the participants in the education process and also setting up and adapting the education process to them, diff erent styles of learning etc.).
Keywords: adult education; clearly defined education criteria; izobraževanje odraslih; jasno zastavljeni kriteriji izobraževanja; predstavitev seminarske naloge; seminar presentation; social anxiety; socialna anksioznost; vzgoja in izobraževanje